Temperature sensor based on modal interference in hollow-core photonic bandgap fiber with collapse splicing - Gong, Huaping (2013)
A temperature sensor based on modal interference in a hollow-core photonic bandgap fiber (HC-PBGF) is presented. The modal interferometer is fabricated by splicing the two ends of a 12-mm HC-PBGF to the standard single-mode fibers. The airholes in the core and cladding of the HC-PBGF are completely collapsed during the fusion splicing, and the length of the collapsed area of about 300 μm is observed. The transmission spectra under different temperatures are measured. The sensitivity of 31.8 pm/°C is achieved in the range of 25 °C-60 °C. The influence of the length of HC-PBGF on the sensitivity is also investigated.